2017
DOI: 10.2174/1874434601711010108
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Adult Nursing Turnover: A Systematic Review of Systematic Reviews

Abstract: Background:Nurse turnover is an issue of concern in health care systems internationally. Understanding which interventions are effective to reduce turnover rates is important to managers and health care organisations. Despite a plethora of reviews of such interventions, strength of evidence is hard to determine.Objective:We aimed to review literature on interventions to reduce turnover in nurses working in the adult health care services in developed economies.Method:We conducted an overview (systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…at the micro‐organisational level) in developed economies (Halter et al . ). Against this paucity of empirical evidence, there is a need to draw on the evidence from experience, i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…at the micro‐organisational level) in developed economies (Halter et al . ). Against this paucity of empirical evidence, there is a need to draw on the evidence from experience, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…at the individual level) and for leadership that creates group cohesion (i.e. at the micro-organisational level) in developed economies (Halter et al 2016b). Against this paucity of empirical evidence, there is a need to draw on the evidence from experience, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors have already been identified as influencing factors towards the retention of community nurses as shown above. However, drawing from the wider literature, a number of studies have considered why hospital nurses leave employment and many of these studies cite job satisfaction (Lu et al, 2012), effectiveness of nurse managers (Halter et al, 2017), staffing levels (Hairr et al, 2014), work autonomy and collegial relationships (Duffield et al, 2014) as influencing factors. No doubt, some of these factors mirror those highlighted above.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown how many community nurses and how many hospital nurses have taken this approach or have identified opportunities elsewhere. Overall, literature shows the absence of effective and efficient models considering organisational, professional and personal factors, impinging the development of interventions capable of improving the retention of nursing workforce (Halter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research done previously has shown that retention is proven to be a better solution to recruitment when dealing with staffing shortages (Halter et al, 2017). Doran suggests that it is time for the concerned authorities to work on keeping Irish nurses in Ireland and in the public sector.…”
Section: Recommendationsmentioning
confidence: 99%